On Christian doctrine and selected introductory works - Augustine, of Hippo, Saint, 354-430 (Theological foundations (B&H Academic), 2022)
The Theological Foundations series highlights the enduring influence of prominent figures from church history. This volume features four works by Augustine of Hippo, along with an introduction by series editor Timothy George that explores Augustine's intellectual and pastoral impact today. Scholars, pastors, and students alike may take up, read, and learn from these masterpieces penned by one of church history's most iconic theologians.